2017
DOI: 10.1002/jts.22157
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐Analysis of the Association Between Appraisals of Trauma and Posttraumatic Stress in Children and Adolescents

Abstract: Cognitive models of posttraumatic stress disorder (PTSD) place an emphasis on the role of negative appraisals of traumatic events. It is suggested that the way in which the event is appraised determines the extent to which posttraumatic stress symptoms will be experienced. Therefore, a strong relationship between trauma appraisals and symptoms of PTSD might be expected. However, this relationship is not as firmly established in the child and adolescent literature. A systematic literature review of this relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 22 publications
10
40
0
Order By: Relevance
“…These results are consistent with previous studies showing that participants with dysfunctional cognitions also report the presence of PTSD symptomatology (Kaczkurkin et al, 2017;Mitchell, Brennan, Curran, Hanna, & Dyer, 2017). In addition, we showed that specific cognitions related to driving situations are associated with PTSD symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with previous studies showing that participants with dysfunctional cognitions also report the presence of PTSD symptomatology (Kaczkurkin et al, 2017;Mitchell, Brennan, Curran, Hanna, & Dyer, 2017). In addition, we showed that specific cognitions related to driving situations are associated with PTSD symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, if people are concerned about having an accident, about people's opinion on his or her driving behaviour, or about being panicked while driving, this may exacerbate the posttraumatic symptomatology. These results are consistent with previous studies showing that participants with dysfunctional cognitions also report the presence of PTSD symptomatology (Kaczkurkin et al, ; Mitchell, Brennan, Curran, Hanna, & Dyer, ). In addition, we showed that specific cognitions related to driving situations are associated with PTSD symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…The significant cross-sectional correlations at each assessment, in line with our second hypothesis, confirmed previous findings on the association between dysfunctional posttraumatic cognitions and PTSS (see Mitchell, Brennan, Curran, Hanna, & Dyer, 2017) as well as their association with internalizing and externalizing problems (Leeson & Nixon, 2011;Liu & Chen, 2015). They are also in line with the findings reported in a nationally representative German sample in which youth affected by violence showed both internalizing and externalizing mental health problems, and they also exhibited significantly higher rates of cumulative mental health problems (Schlack & Petermann, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Cognitive-emotional models of PTSD (Ehlers and Clark 2000;Foa et al 2006) suggest overly generalizing, catastrophizing or otherwise maladaptive posttraumatic appraisals to be crucial to the development and maintenance of and recovery from PTSS. This is supported by empirical evidence demonstrating that such PTCs feature heavily in the development and maintenance of PTSS both among adults (Hansen et al 2014;Karl et al 2009;LoSavio et al 2017;Nixon and Bryant 2005) and children (Mitchell et al 2017). Our findings here and those of previous reviews (Sripada et al 2016;Zalta 2015) lend further credence to this view.…”
Section: Evidence For Different Mechanismsmentioning
confidence: 65%